Temporal passage and the ‘no alternate possibilities’ argument - Tallant, Jonathan (Universidade Estadual de Campinas, Faculdade de Educação, 2016)
Dynamic theories of time typically commit to the claim that “time passes”. In this paper I develop a version of the ‘no alternate possibilities’ argument in order to show that time does not pass, but that this is no threat to dynamic theories of time.